2019
DOI: 10.1017/dmp.2018.94
|View full text |Cite
|
Sign up to set email alerts
|

Response Functions in Disasters: Iran Flash Flood 2016

Abstract: Objective:Heavy rain and flash flooding left behind a trail of disaster in the western and south-western provinces of Iran in April 2016. The purpose of this study is to highlight the response functions that should be undertaken when such disasters strike.Methods:Secondary data, such as documents, organizational reports, and forms completed during response to the flood visits, were the methods of data collection in this study. Then, collected data were analyzed according to the response functions to disasters.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…Other studies have also confirmed these actions as part of the flood response plan (Cvetkovi c et al, 2018;JICA, 2014;WHO, 2019). Also, the Ardalan study, which examined disaster response functions in a flash flood, validates these findings (Dizaji et al, 2019). According to our results, intra and interorganizational information exchange is very important during information management activities.…”
Section: Initial Functionsupporting
confidence: 82%
“…Other studies have also confirmed these actions as part of the flood response plan (Cvetkovi c et al, 2018;JICA, 2014;WHO, 2019). Also, the Ardalan study, which examined disaster response functions in a flash flood, validates these findings (Dizaji et al, 2019). According to our results, intra and interorganizational information exchange is very important during information management activities.…”
Section: Initial Functionsupporting
confidence: 82%
“…In Abbaszadeh study, the functions of the Iranian health system in response to sudden floods include Rapid Assessment, Warning and Event Confirmation, Establishing Incident Command Posts, Codifying the Incident Action Plan, Command and Control, Logistics, Public Communication, and Information Management. [ 26 ] However, the important point of using this method is that in the planning process of large-scale events, especially biological events related to public health, any decision, no matter how small, must be carefully considered. However, research by Frederick[ 27 ] shows that some functions, including the incident command system, are not capable of handling the complexity of major health disasters, especially epidemics.…”
Section: Discussionmentioning
confidence: 99%